5 REASONS BEHIND THE FAILURE OF THE STARTUPS - Habibullayev Samandar; Saidov Sardor; Shavkatxodjayev Rasulxo’ja (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This paper explores major causes of startup failures, and common barriers  to  business  success.  Although  startups  are  new  ventures  with  great entrepreneurial potential and rate of development, they fail because of weak business models, wrong positioning of products on the market, internal conflicts, lack of finance, and high  competition.  The  paper  examines  literature  and  conducts  interviews  with startup owners and identify some of the problems that plague many start-ups including the focus on product development and the wrong revenue models that may not respond to market needs. Based on real life examples of Quibi, Theranos and Juicero, the study delivers  key  take-aways  and  suggested  frameworks  that  focus  on  robust  business models, identifying the right market, building the right team, financial management and developing competitive differentiation to improve startup outcomes.